Influence of Doping Conditions on the Properties of Nickel Atom Clusters - Ismailov, Kanatbay A.; Saparniyazova, Zlikha M.; Kudeshova, Gulchekhra T.; Seytimbetova, Gulbadan A.; Saparov, Fayzulla A. (East European Journal of Physics, 2024)
It is shown that the dynamics of changes in the state of nickel clusters depends on the temperature of the diffusion maximum and the cooling rate. It was found that with increasing annealing temperature and cooling rate, an increase in density and a decrease in cluster size are observed. In this case, the main attention was paid to the determination of the laws governing the change in the density, size, and structure of clusters from temperature and cooling. The process and dynamics of the interaction of clusters depends on the diffusion coefficient of impurity atoms in the lattice and the level of supersaturation of the solid solution. It has been established that with a change in the annealing temperature from T = 1100℃ to 1250℃, the cluster density increases by almost 1-1.5 orders of magnitude, and their size decreases by a factor of 5–6. It seems to us that to obtain clusters with stable parameters, the optimal cooling rate is 200–300℃.